2021
DOI: 10.3390/app11020680
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biopreparations and Biostimulants on the Chemical Composition and Microorganisms Associated with Verticillium Wilt of Horseradish Roots (Armoracia rusticana Gaertn.)

Abstract: The basic foundation of plant production consists in plant protection treatments, which largely shape the quality of plant raw material intended for the food industry. Due to its long growing season, horseradish requires more treatments than average. Intensive protection based on synthetic pesticides favours the accumulation of their residues in plants and generates serious environmental problems. We have examined the effect of chemical protection and its reduced variant as well as three variants of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Cytokinins have an impact on the enhancement and growth of the plant root system [106,107]. Therefore, the results obtained are not surprising; they only confirm the yield-enhancing role of PGPEm [108][109][110]. The conducted research study has shown that PGPEm protects potato tubers against silver scurf better than MSADs (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Cytokinins have an impact on the enhancement and growth of the plant root system [106,107]. Therefore, the results obtained are not surprising; they only confirm the yield-enhancing role of PGPEm [108][109][110]. The conducted research study has shown that PGPEm protects potato tubers against silver scurf better than MSADs (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…The representative of the kingdom of Chromista (class Oomycetes), Pythium oligandrum, is one of the best-known organisms used in plant protection for the longest [43,44,95,96]. According to Brozowa [97], P. oligandrum contributes to an increase in the soil population of antagonists, which reduces the density of many important pathogens, including R. solani.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations